(untitled) (Research, Society and Development, 2021)
This objective research will identify the methodological aspects applied during clinical simulation, and map the contribution of clinical simulation without training of cardiopulmonary resuscitation for the development of professional competencies. This is a scoping review carried out on the PUBMED, Lilacs, Cochrane databases, and on the SciELO site, during or over May 2020. It follows the recommendations of The Joanna Briggs Institute and the PRISMA-SCR stages. The studies identified were endorsed by a pair of researchers. The data are synthesized, organized in categories and presented by means of a figure and squares. There were 337 articles identified, 12 included in this review. The methodological aspects identified are related to educational practices, fidelity, realism, skills / support to the participant and or debriefing conducted by the facilitator. The analysis of two studies shows that the clinical simulation for cardiopulmonary resuscitation training contributes to the development of professional competencies such as knowledge, technical and non-technical skills, attitudes, self-confidence, critical thinking, training in clinical responsibility, work in situational equipment, ea satisfaction as learned. The contributions to the simulation are clear and allow the development of diversified professional competitions. Although the methodological aspects related to simulation have been described, they lack the theoretical background for the research to be reproduced in other professionais settings. This scoping confirms that this teaching method adds knowledge and develops competencies, and therefore, is recommended for the training of adult, pediatric and neonatal cardiopulmonary resuscitation for those who are professionals of the health team such as nurses, doctors and physiotherapists.